Population genetic studies on the Anopheles minimus complex in Thailand. - S. Sucharit (2018)
The population genetic studies on the Anopheles minimus complex revealed that An. minimus is a species complex evident by IK value were less than 0.0534 and 0.4163 for the morphotaxonomy and isozyme studies. There are two sibling species in the An. minimus species complex. The first is the typical minimus and its variations described by Harrison. Esterase-2 alleles 100 and 102 are predominant with a few other alleles of 96 and 104. It is exophagic and zoophilic. It is widely distributed in all provinces where minimus breeds. The second of the two sibling species is An. minimus species C, with 2 pale spots on the humeral dark band and Est-2 allele 98. It is found most frequently in Pu Toei District of Kanchanaburi Province, Thailand. An. minimus probably species B showing M1 + 2 wing vein entirely dark is found in China.